Evaluating emergency preparedness and impact of a hurricane sandy in pediatric patients with diabetes. Issue 1 (December 2016) - Heptulla, Rubina; Hashim, Rebecca; Johnson, Doreen; Ilkowitz, Jeniece; DiNapoli, Gina; Renukuntla, Venkat; Sivitz, Jennifer
Abstract Background Natural disasters have always been associated with significant adverse events including medical and mental health problems. Children with chronic disease such has diabetes have also been believed to be affected to a greater extent by any natural disaster. The purpose of this study was to assess and compare emergency preparedness post-disaster and post-traumatic stress effects of Hurricane Sandy in affected and relatively unaffected populations. Methods The study was conducted between February and July 2013. A total of 142 families caring for children with Type 1 Diabetes Mellitus (T1DM) who attended clinics were recruited from hospitals in Bronx, NY (control) and in NJ (affected) by Hurricane Sandy. Subjects were recruited to participate in a survey 3–6 months after the hurricane. Data on demographics, glycemic control and insulin regimens were collected. Families were surveyed for socio-economic status (SES), using Hollingshead questionnaire, general and diabetes preparedness and the Hurricane Related Traumatic Experiences (HURTE) questionnaire was used to evaluate for symptoms of post-traumatic stress. Results Ninety-five percent of families reported to be generally well to moderately prepared for the hurricane and 83 % reported to be very well prepared with regards to their child's diabetes during the disaster. There was no difference between the sites for preparedness for the disaster, age or gender. There was a trend toward significance (p < 0.06) in New Jersey subjects as to a greater psychological impact from the hurricane. Poor glycemic control was significantly associated with lower SES (p < 0.008). Most importantly, SES was unrelated to preparedness for diabetes management during the hurricane. Conclusions Despite low SES, families were generally well to moderately prepared for hurricane. In children with diabetes, interventional studies should be designed and implemented so that glycemic control remains unaffected, following any major disaster.